FAKTOR-FAKTOR BERPENGARUH BAGI KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sri Elviani (Universitas Islam Islam Sumatera Utara, 2018)
Problem in this research is timeliness in the delivery of financial statements. Based on data in Indonesia Stock Exchange, there were 49 companies in 2014 which delayed delivering financial statements of December 31st on 2013, while in 2015 there were 52 companies late delivering the audit financial statements of 31st December 2014. This phenomenon is interesting to be observed due to the timeliness of delivery financial statements are a reflection of the credibility of reported quality of information and a reflection of the level of compliance with established regulations. Timeliness is one of the important factors in presenting relevant information, because the information of financial statements submitted in a timely manner will reduce the asymmetry of information closely related to agency theory. In this research, several factors that are assumed to have an effect on the accuracy of financial statements in Indonesia Stock Exchange are debt to equity ratio, profitability, ownership structure, auditor quality, and auditor turnover. Therefore testing of the five factors will be the focus in this study. This research method based on quantitative descriptive method with the nature of research is associative. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange, while taking samples using purposive sampling method, ie the selection of non-random samples whose information is obtained with certain considerations. This research uses descriptive statistical analysis method and and multiple regression analysis. The results show that debt to equity ratio has no effect on the timeliness of corporate financial reporting. While profitability affects the timeliness of corporate financial reporting, as well as the ownership structure affects the timeliness of corporate financial reporting. The quality of auditors does not affect the timeliness of corporate financial reporting.